A green synthesis of palladium nanoparticles by Sapindus mukorossi seed extract and use in efficient room temperature Suzuki–Miyaura cross‐coupling reaction. (10th April 2017) - Borah, Raju Kumar; Mahanta, Abhijit; Dutta, Anurag; Bora, Utpal; Thakur, Ashim J.
Abstract : A simple and green method for the synthesis of palladium nanoparticles using an aqueous extract of Sapindus mukorossi seed has been demonstrated. The synthesized nanoparticles were characterized using UV–visible spectroscopy, powxder X‐ray diffraction, energy‐dispersive X‐ray analysis and transmission electron microscopy. The nanocatalyst was successfully utilized in an efficient Suzuki–Miyaura cross‐coupling reaction at room temperature. Abstract : A simple and green method for the synthesis of palladium nanoparticles using an aqueous extract of Sapindus mukorossi seed has been demonstrated. The synthesized nanoparticles were characterized using various methods. The nanocatalyst was successfully utilized in an efficient Suzuki–Miyaura cross‐coupling reaction at room temperature.